(5) (ii) ((5^2)^3×5^4)÷5^6 simplify and give reasons
answer:
((5^2)^3×5^4)÷5^6
((5)^2×3×5^4)/5^6 (therefore (a^m)^n/a^mn)
=5^6×5^4/5^6(therefore a^m×a^n=a^m+n)
5^6+4/5^6=5^10/5^6=5^10-6 (therefore a^m/a^n=a^mn)
=5^4=625 (therefore 5^4=5×5×5×5)
Answers
Answered by
2
Answer:
(1/2)5 = 243 / 7,776 = 0.03125
Step-by-step explanation:
Answered by
12
Answer:
5^10/5^6=5^10-6=5^4=625
Step-by-step explanation:
(a^m)^n=a^mn
(5^2×3)×5^4÷5^6
(5^6)×5^4÷5^6
a^m×a^n=a^m+n
5^6+4÷5^6=5^10÷5^6
5^10/5^6
a^m/a^n=a^m-m
5^10/5^6=5^10-6=5^4=625
hope this is help for u
thank u
Similar questions
Social Sciences,
5 months ago
Social Sciences,
5 months ago
English,
11 months ago
English,
1 year ago
Math,
1 year ago